Ibuprofen-loaded PCL meshes manufactured using rapid tooling for ocular orbital repair. (September 2017) - Salmoria, Gean V.; Sibilia, Francesca; Gindri, Izabelle M.; Roesler, Carlos R.M.; Farè, Silvia; Tanzi, Maria C.
Abstract: This study investigated the manufacture of resorbable polycaprolactone/ibuprofen (PCL/IBP) meshes by injection molding for application in ocular orbital repair. The pore dimension sizes used demonstrate that micro-porous meshes can be manufactured by injection molding using a prototype mold. The mechanical properties were observed to be dependent on the material composition and morphology. Lower stiffness, strength and elongation at failure were observed for the 8 mm pore sized samples. The PCL/Ibuprofen meshes initially showed a fast drug release but after 3 days the release was slow and controlled. The cytotoxicity test results of the PCL/Ibuprofen meshes indicated that the large initial quantity of Ibuprofen released was too high and resulted in cell toxicity. However, after this initial release, the PCL/Ibuprofen meshes showed a good interaction with the cells seeded on their surface. The presence of a low concentration of Ibuprofen does not negatively influence cell viability in culture.